(untitled) (Global Journals of Research in Engineering, 2022)
Productivity in the modern era has become a common term in any sector Increasing productivity and better use of human and other resources have become a basic need for the development and survival of any organisation Similarly in the industrial sector it holds a very important place For the enhancement of productivity targeting the processes and various operations activities underlying those processes is one of the best ways This can be achieved by the reduction in non-value-added activities and by developing time standards for the improvement of the processes Various work measurement techniques can be used to analyse the time being used to perform an operation and critical analysis of them can help in deciding the standard time for a single operation This study was done to determine the effects of these work measurement techniques on an operation The study uses detailed activity analysis techniques like micro-motion study and for setting time standards it uses a predetermined motion time systems PMTS technique called Maynard Operation Sequence Technique MOST Micro-motion study has an added advantage over time study technique in highly repetitive operations and cycle time for whose is just a few seconds The main purpose of the micro-motion study however is to eliminate non-value added activities from the sequence of the operation and resequencing for optimal movement activities The MOST study is done to set time standards by observing the necessary movements in the sequence of an operation Different families of MOST can be used to analyse an operation based on various factors that need to be considered beforehand Due to the high repetition rate and very low cycle times of the operation considered in this study we are using the MiniMOST technique It is evident from the study done that a considerable reduction in cycle times can be observed going from analysis to standardisation stage A similar procedure can be used to analyse other operations where human intervention is needed